Effect of Dietary Rumen Protected Methionine and/or Choline Supplementation on Rumen Fermentation Characteristics and Productive Performance of Early Lactating Cows - Soltan, M.A.; Mujalli, A.M.; Mandour, M.A.; Abeer, M. El-Shinway (Pakistan Journal of Nutrition, 2012)
Sixty early lactating Holstein dairy cows were fed for 12 weeks on berseem hay and cereal grains based total mixed ration formulated with the MET content limited (40 g/day) to investigate the effect of supplementing rumen protected methionine (15 g/day) and/or choline (30 g/day) on rumen fermentation characteristics, productive performance and some blood serum parameters. Cows were allotted into four groups and fed on the basal diet without supplementation, supplemented by 15 g/day of RP-MET, 30 g of RP-CHOL or 15 g MET + 30 CHOL respectively. Average body weight was not significantly different among treatment, but cows fed on basal diet supplemented by both RP-MET and RP-CHOL was mobilizing less body tissue in the post-partum period. RP-MET improved (p<0.05) DMI by 0.7% when compared with MET limited group, while RP-CHOL significantly improved DMI by 8.4% throughout the whole experimental period when compared with the control group cows. There was an improvement of milk production with RP-MET supplementation by 2.5% across the whole experimental period when compared with MET limited group, while RP-CHOL improved milk production by 5.9 and 3.3% when compared with cows fed on the control basal diet and both MET and CHOL treated diets, respectively. Milk protein yield tended to increase with RP-MET and RP-CHOL supplementation by 5.3 and 7.4% when compared with cows fed on the basal diet without supplement. Both RP-MET and RP-CHOL improved ECM and milk-to-feed ratio but had no significant effect on rumen fermentation characteristics. Rumen protected MET induced no significant effect on blood serum glucose, triglyceride, NEFA and blood urea concentration while reduced (p<0.05) blood serum cholesterol when compared with MET limited group. Moreover, RP-CHOL significantly increased blood serum glucose and cholesterol concentration and reduced triglyceride, NEFA and urea concentrations. It could be concluded that Dietary RP-CHOL (30 g/day) to early lactating dairy cows that received a MET limited diet improved DMI, milk yield and increased milk protein yield. In conclusion, supplementing RP-MET (15 g/day) or both RP-MET + RP-CHOL were not beneficial as RP-CHOL supplementation alone.